Technique Creates High-Performance Storage Technology. - Paulson, Linda Dailey (Computer (00189162), 2007)
The article reports on advances in computer storage technology current in August 2007. Through the use of electric pulses researchers have found that a computer's capacity to store data can be increased to a significant degree, along with improvements in the speed and reliability of computer systems. The article explains that scientists achieved their results by replacing a traditional computer disk drive with an extremely small wire composed of nickel and iron and subjecting it to brief electrical pulses.